Credit Risk, Liquidity, and Financial Stability: An Investigation in the Indonesian Banking Sector - Faaza Fakhrunnas (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2026)
Research Originality: This study offers a clear and precise investigation into the relationship between credit risk, liquidity, and financial stability, addressing the inconclusive findings in prior literature. In addition, a nonlinear approach is adopted to capture the dynamic interaction of credit risk and liquidity on financial stability Research Objectives: The study aims to assess the influence of Islamic banks' credit risk and liquidity on financial stability in the Indonesian banking sector. Research Method: Utilizing time series data ranging from 2004m1 to 2022m8, a nonlinear autoregressive distributed lag (NARDL) approach is adopted to measure the impact of credit risk and liquidity on financial stability. Empirical Results: The findings of the study reveal that it has nonlinear, symmetric, and asymmetric effects between independent variables and dependent variables. In the short run, only credit risk has a significant relationship, while in the long run, either credit risk or liquidity affects financial stability significantly. Implications: The study's results imply that Islamic banks must implement liquidity monitoring and a credit risk early warning system. At the regulatory level, tailor-made liquidity instruments and encouraging Islamic banks to have a larger capital buffer need to be introduced and regulated. JEL Classification: G20, G21, G29